THE EFFECT OF MACRO VARIABLES ON SHARIA STOCK RETURNS - Surono, Surono; Hamdi, Hamdi; Kumar, Prodib (Al-Mashrof: Islamic Banking and Finance, 2022)
This study aims to analyze whether there is an effect of inflation and exchange rates on Islamic stock returns in the property and real estate sectors listed on ISSI (Indonesian Sharia Shares Index) for the period 2012-2018). The population of this study is all sharia shares in the property and real estate sector registered at ISSI for the period 2012-2018. The type of data used is secondary data obtained through published annual reports which were analyzed using multiple linear regression with the help of the E-Views Program. The results of this study are: inflation and exchange rates partially have no effect on the return of sharia shares in the property and real estate sectors listed on ISSI (Indonesian Sharia Stock Index) for the period 2012-2018. Then inflation and exchange rates simultaneously show that there is no effect on the return of sharia shares in the property and real estate sectors listed on the ISSI (Indonesian Sharia Stock Index) for the period 2012-2018. finally Exchange rate inflation and stock returns in the perspective of Islamic economics will have a good impact when utilizing a certain item to fulfill every need according to the need or portion and not following their desires. Based on the results of this study, it can be concluded that inflation and exchange rates cannot be taken into account in determining stock investment decisions in the Islamic perspective for the period 2012-2018. The Islamic economic perspective views that in terms of both investment and macroeconomics, when carried out with Sharia economic principles, it can benefit anyone and society will prosper.